Transforming international student recruitment: The role of AI, personalization, and trust in Jordanian higher education - Al-Dmour, Hani; Al-Dmour , Rand; Al-Dmour , Yazeed; Al-Dmour , Ahmed (Journal of International Students, 2025)
In this study, we examine the role of AI-driven marketing in international student recruitment, focusing on how perceived usefulness, trust, and personalization influence decision-making. Grounded in the Technology Acceptance Model (TAM), the Trust-Based Decision-Making Model, and the Personalization‒Privacy Paradox, we studied how AI-powered recruitment tools—such as chatbots, predictive analytics, and personalized content—impact student engagement and enrollment intentions. Based on the responses from 350 prospective international students, the findings indicate that AI-driven marketing enhances student recruitment by improving accessibility, engagement, and transparency. However, trust in AI remains critical, as concerns about data privacy and algorithmic bias significantly influence students’ willingness to apply it. Additionally, AI-powered personalization significantly affects decision-making by making recruitment more efficient and tailored to students’ preferences; however, it also raises ethical concerns regarding privacy and data protection.